Evaluation of carcass characteristics and meat chemical composition of Bos indicus and Bos indicus x Bos taurus crossbred steers finished in pasture systems - Moreira,Fernanda Barros (2003)
The objective of this study was to evaluate the carcass characteristics (carcass weight, carcass yield, fat thickness, loin area, marbling and colour) and chemical composition of the Longissimus dorsi muscle (moisture, ash, crude protein, fat and cholesterol) of cuts with or without fat thickness, of Bos indicus and Bos indicus x Bos taurus crossbred steers finished in millet (Pennisetum americanum L.) or star grass (Cynodon plectostachyus Pilger) pasture systems, with mineral or mineral protein supplementation. Animals were slaughtered with an average body weight of 450 kg (Bos indicus) or 470 kg (Bos indicus x Bos taurus crossbreed). There was no treatments effect on carcass characteristics and meat chemical composition of cut without fat thickness. The cuts with fat thickness of steers fed millet presented the highest fat deposition. Bos indicus steers presented higher carcass yield (57.23%) and fat thickness (4.88 mm) compared with crossbreed (53.40% and 3.05 mm). There was no breed effect on chemical composition of meat. The mean levels of cholesterol concentration were 31.41 mg/100 and 37.55 mg/100g of meat with and without fat thickness.